The association of vitamin D with survival in colorectal cancer patients depends on antioxidant capacity - Boakye, Daniel; Jansen, Lina; Schöttker, Ben; Jansen, Eugene H J M; Halama, Niels; Maalmi, Haifa; Gao, Xin; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (The American journal of clinical nutrition, 2021)
Vitamin D plays a role in detoxifying free radicals, which might explain the previously reported lower mortality in colorectal cancer (CRC) patients with higher vitamin D concentrations.We aimed to assess whether the associations of 25-hydroxyvitamin D [25(OH)D] with prognosis in CRC patients differ by total thiol concentration (TTC), a biomarker of antioxidant capacity.CRC patients who were diagnosed from 2003 to 2010 and recruited into a population-based study in southern Germany (n = 2,592) were followed over a period of 6 y. 25(OH)D and TTC were evaluated from blood samples collected shortly after CRC diagnosis. Associations of 25(OH)D with all-cause and CRC mortality according to TTC were estimated using multivariable Cox proportional hazards regression.There was a weak positive correlation between 25(OH)D and TTC (r = 0.26, P < 0.001). 25(OH)D was inversely associated with mortality among patients in the lowest and middle TTC tertiles, but no associations were found among patients in the highest TTC tertile (P-interaction = 0.01). Among patients in the lowest/middle TTC tertiles, those in the middle and highest (compared with lowest) 25(OH)D tertiles had 31% and 44% lower all-cause mortality (P < 0.001) and 25% and 45% lower CRC mortality (P < 0.001), respectively. However, in the highest TTC tertile, 25(OH)D was not associated with all-cause (P = 0.638) or CRC mortality (P = 0.395).The survival advantages in CRC patients with adequate vitamin D strongly depend on antioxidant capacity and are most pronounced in cases of low antioxidant capacity. These findings suggest that TTC and other biomarkers of antioxidant status may be useful as the basis for enhanced selection criteria of patients for vitamin D supplementation, in addition to the conventional judgment based on blood 25(OH)D concentrations, and also for refining selection of patients for clinical trials aiming to estimate the effect of vitamin D supplementation.